Pengaruh Ekuitas Merek dan Promosi Terhadap Keputusan Pembelian Sepeda Motor Yamaha oleh Warga RW.010 di Kelurahan Kranji - Pius Sanjoyo; Henny Armaniah (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2023)
The very rapid development of the automotive industry in Indonesia has made the level of competition intense, especially in the motorbike industry, so that motorbike manufacturers continue to innovate their products. Despite innovation, Yamaha motorbike sales tend to fall every year. This indicates that people's buying interest in Yamaha motorbikes is starting to decline. This research aims to determine and analyze the influence of brand equity and promotion on the decision to purchase Yamaha motorbikes by residents of Kranji Village. The type of research used was explanatory research with a quantitative approach, involving 100 samples who were residents of RW.010 Kranji Village who were at least 17 years old and who used Yamaha motorbikes. Data were analyzed using SPSS software with a non-probability sampling technique using a purposive sampling method. The data analysis method used is multiple linear regression analysis. The research results show that partially, brand equity and promotion variables have a positive and significant influence on purchasing decisions. The F test results also show that brand equity and promotion simultaneously have a positive and significant effect on purchasing decisions.